Aplikasi Bahan Organik dan Biochar untuk Meningkatkan C – Organik, P dan Zn tersedia Pada Tanah Sawah - R. Ayu Chairunnisya Chairunnisya; Hamidah Hanum; Benny Hidayat (Universitas Sumatera Utara, 2017)
The yield of rice crops that have been fertilized intensively by used inorganic fertilizer with high dosecan caused decline of land productivity. The purpose of this research was to know the effect of organicmatter application to increasing organic carbon, P – available, and Zn - available in paddy soil. Thisexperiment was conducted in green house and Laboratory of Research and Technology AgricultureFaculty Univesity of Sumatera Utara, Medan from March until July 2016. Soil samples were takenat Lubuk Dendang village, Serdang Bedagai district. The research used non factorial randomizedcomplete design with eight treatments and three replications, consist of A (control), B (cow manure10 ton/ha), C (rice husk biochar 10 ton/ha), D (straw compost 10 ton/ha), E (cow manure + rice huskbiochar 20 ton/ha), F (cow manure + straw compost 20 ton /ha), G (rice husk biochar + straw compost20 ton/ha), and H (cow manure + rice husk biochar + straw compost 30 ton/ha). Parameters observedare include soil pH, organic carbon, P – available and Zn – available. The result showed that all kindof organic matters and biochar which used in this research have no effect on increasing soil pH, Zn –available but have same effect on increasing organic carbon and P – available.Key words : biochar, organic carbon, organic matters, P – available, Zn -available